Characterization of a novel HESX1 mutation in a pediatric case of septo‐optic dysplasia. Issue 4 (2nd March 2017) - Pozzi, Sara; Tan, Wen‐Hann; Martinez‐Barbera, JuanPedro
Key Clinical Message: Septo‐optic dysplasia (SOD) is a rare condition for which the precise etiology is still unclear. Elucidating the genetic component of SOD is a difficult but necessary task for the future. We describe herein a novel HESX1 c.475C>T (p.R159W) mutation and demonstrate its potential pathogenicity in the development of this rare disease. Abstract : Septo‐optic dysplasia (SOD) is a rare condition for which the precise etiology is still unclear. Elucidating the genetic component of SOD is a difficult but necessary task for the future. We here describe a novel HESX1 c.475C>T (p.R159W) mutation and demonstrate its potential pathogenicity in the development of this rare disease.